Technical and tactical diagnosis model of table tennis matches based on BP neural network - Huang, W.; Lu, M.; Zeng, Y.; Hu, M.; Xiao, Y. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background The technical and tactical diagnosis of table tennis is extremely important in the preparation for competition which is complicated by an apparent nonlinear relationship between athletes` performance and their sports quality. The neural network model provides a high nonlinear dynamic processing ability and fitting accuracy that may assist in the diagnosis of table tennis players` technical and tactical skill. The main purpose of this study was to establish a technical and tactical diagnosis model of table tennis matches based on a neural network to analyze the influence of athletes` techniques and tactics on the competition results.